2022
DOI: 10.1002/edn3.384
|View full text |Cite
|
Sign up to set email alerts
|

Development and field validation of RPA‐CRISPR‐Cas environmental DNA assays for the detection of brown trout (Salmo trutta) and Arctic char (Salvelinus alpinus)

Abstract: Isothermal molecular techniques offer an alternative to single taxa monitoring using environmental DNA (eDNA). Methodologies such as Loop-Mediated Amplification (LAMP) (Notomi et al., 2000) and Recombinase Polymerase Amplification (RPA) (Piepenburg et al., 2006) have been readily adopted for point-of-care diagnostics (Craw & Balachandran, 2012;Oliveira et al., 2021), but use in environmental monitoring remains limited. Despite this, previous studies have shown successful detection of, for example, Dreissena sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…For instance, in the first application of Cas12a‐based detection, termed DETECTR (sensu Chen et al., 2018), on eDNA samples, Williams et al. (2019) used a 50 nM final concentration of FAM‐labelled ssDNA, which required a 2‐h incubation and assistance by a qPCR instrument to detect the fluorescence emitted by the reporter molecules (though see modifications in Williams et al., 2023). FINDeM, however, uses a ROX‐labelled ssDNA at a 1 μM final concentration, as Xie et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the first application of Cas12a‐based detection, termed DETECTR (sensu Chen et al., 2018), on eDNA samples, Williams et al. (2019) used a 50 nM final concentration of FAM‐labelled ssDNA, which required a 2‐h incubation and assistance by a qPCR instrument to detect the fluorescence emitted by the reporter molecules (though see modifications in Williams et al., 2023). FINDeM, however, uses a ROX‐labelled ssDNA at a 1 μM final concentration, as Xie et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although our presentation of a field-deployable, CRISPR-based system for organism detection stands as a novelty in ecology, many of the methodological decisions made in this study came because of the integration of prior attempts from other systems. For instance, in the first application of Cas12a-based detection, termed DETECTR (sensu Chen et al, 2018), on eDNA samples, Williams et al ( 2019) used a 50 nM final concentration of FAM-labelled ssDNA, which required a 2-h incubation and assistance by a qPCR instrument to detect the fluorescence emitted by the reporter molecules (though see modifications in Williams et al, 2023). FINDeM, however, uses a ROX-labelled ssDNA at a 1 μM final concentration, as Xie et al (2021) found that using ROX-labelled ssDNA exhibited lower ambiguity between positive and negative results, showed greater emission of fluorescence at lower ssDNA concentrations and even allowed for naked-eye detection when used at higher concentrations.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The CRISPR-Dx eDNA methods published to date using Cas12a (Williams et al, 2019(Williams et al, , 2021(Williams et al, , 2022 and Cas13a (described herein)…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR‐Dx eDNA methods published to date using Cas12a (Williams et al., 2019, 2021, 2022) and Cas13a (described herein) utilize RPA for initial target amplification, followed by subsequent detection by a CRISPR system. In combination, RPA amplification and SHERLOCK detection allow specific, isothermal, high‐sensitivity detection.…”
Section: Discussionmentioning
confidence: 99%
“…In the coming years, we expect major improvements in various aspects of fish sedDNA sampling design, extraction and purification techniques, detection methods, and data analysis and interpretation. Specifically, we anticipate the following advancements in the field of fish sedDNA: (1) development in sequencing platforms and emerging detection approaches (e.g., hybridization‐capture, RPA‐CRISPR; Williams et al, 2023; Williams et al, 2021; Williams et al, 2019) to reduce costs while improving limits of detection; (2) development of controlled experiments to validate, better understand, and calibrate the taphonomic processes behind fish sedDNA; (3) collaborations with geochemists and other researchers to better characterize the binding properties of DNA with complex and variable sediment matrices; (4) improvement of methods to concentrate and detect rare or degraded fish sedDNA without co‐concentrating PCR‐inhibitors; (5) expansion of efforts to improve the accuracy and augment fish DNA reference sequence database resources; (6) integration of fish sedDNA studies with indigenous and local ecological knowledge; (7) expansion of fish sedDNA studies to more diverse regions and communities to help identify the best methods for particular settings and contexts; (8) development of analytical approaches to better statistically account for incomplete detection and time scale biases; and (9) standardization of sampling, metadata processing, and reporting to increase the confidence and repeatability of fish sedDNA‐inferred biological data.…”
Section: Future Directionsmentioning
confidence: 99%